Understanding and forecasting phreatic eruptions driven by magmatic degassing - Stix, John (2018)
This work was supported by Discovery and Accelerator grants to JS from the Natural Sciences and Engineering Research Council of Canada, and funding to MdM from Costa Rican Ley Transitorio 8933 and the Deep Carbon Observatory Biology Meets Subfunction project.